1997
DOI: 10.1002/(sici)1096-9861(19970210)378:2<239::aid-cne7>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Localization of AMPA-selective glutamate receptors in the auditory brainstem of the barn owl

Abstract: AMPA receptor subunit-specific antibodies were used to determine if the distribution of excitatory amino acid receptors in the owl's auditory brainstem and midbrain nuclei reflected specializations for temporal processing. Each auditory nucleus displays characteristic levels of immunostaining for the AMPA receptor subunits GluR1-4, with high levels of the subtypes which exhibit rapid desensitization (GluR4 and 2/3). In the auditory brainstem, levels of GluR2/3 and GluR4 were very high in the cochlear nucleus m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
31
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 65 publications
(122 reference statements)
10
31
0
Order By: Relevance
“…It should be noted that some variation among these results is due to temperature and age differences. Our data are consistent with previous studies on GluR subunit distributions (Levin et al 1997) and receptor desensitization kinetics (Raman and Trussell 1992) in NA. These "auditory" currents (Parks 2000) are faster than most AMPAR-mediated currents reported from many other areas in the brain, which have decay time constants of several milliseconds or more.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It should be noted that some variation among these results is due to temperature and age differences. Our data are consistent with previous studies on GluR subunit distributions (Levin et al 1997) and receptor desensitization kinetics (Raman and Trussell 1992) in NA. These "auditory" currents (Parks 2000) are faster than most AMPAR-mediated currents reported from many other areas in the brain, which have decay time constants of several milliseconds or more.…”
Section: Discussionsupporting
confidence: 93%
“…Auditory nerve terminals in NA make anatomically smaller, bouton-like synapses (Carr and Boudreau 1991). Immunohistochemical evidence from the barn owl suggests GluR3 and GluR4 are the most prominent AMPAR subunits in NA (Kubke and Carr 1998;Levin et al 1997). AMPA receptors expressed by chick NA neurons have fast desensitization kinetics (Raman et al 1994) and are also calcium permeable (Zhou et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The Rbfox3 protein is a neuron-specific RNA-binding protein which has been demonstrated to be required in the neuronal differentiation of postmitotic neurons in chick spinal cord (Kim et al 2009(Kim et al , 2013. Alternative splice variations are common among neuronal proteins important in the auditory brain stem, especially glutamate receptors GluR1-4, where the flop variation of GluR3/4 enhances rapid signaling (Fabiana Kubke and Carr 1998;Levin et al 1997;Parks 2000;Raman et al 1994;Sugden et al 2002). While this study utilized NeuN expression as a generic neuron-specific marker, the heterogeneity in anti-NeuN labeling we observed in NA might itself be related to neuronal diversity.…”
Section: Neun Expression In the Chick Auditory Brain Stemmentioning
confidence: 99%
“…Rapidly desensitizing AMPA (␣-amino-3-hydroxy-5-methyl-4-isoxazolepropionate) receptors have been identified on NA neurons dissociated from chick embryos [150]. AMPA receptors in the chick NA are highly permeable to divalent cations [228], and NA neurons in the barn owl strongly express immunoreactivity for the AMPA receptor subunits GluR4 and GluR2/3 but not for GluR1 [96]. These results are consistent with the general finding, much better characterized in NM (see below), that brainstem auditory neurons express AMPA receptors with very rapid desensitization and deactivation kinetics and high permeability to Ca 2+ [139].…”
Section: Transmitters and Receptorsmentioning
confidence: 99%
“…Functional studies have shown that AMPA receptors of NM neurons have the fastest known desensitization and deactivation kinetics [150] and that they have inwardly rectifying current-voltage relationships, high permeability to divalent cations and high sensitivity to block by polyamine toxins [136,153,228]. Structural studies of these receptors have shown that they consist largely of GluR3 and GluR4 subunits expressed in the rapidly desensitizing flop splice variants and that expression of GluR2, which normally prevents permeability to divalent cations, is almost completely abolished during development by both transcriptional and posttranscriptional controls [96,153,196].…”
Section: Ionotropic Glutamate Receptorsmentioning
confidence: 99%